PENGARUH KEPUASAN KONSUMEN TERHADAP KOMUNIKASI WORD OF MOUTH DAN NIAT PEMBELIAN KEMBALI PRODUK DAN JASA DI KLINIK KECANTIKAN LONDON BEAUTY CENTRE YOGYAKARTA - , Kartika Sako, Slamet Santoso Sarwono, Dr., MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Problem of this research begins from many emerging beauty clinics in Indonesia. Tough competition makes The clinic owners compete to offer the best products and services to reach the consumer satisfaction. Consumersâ satisfaction is an important asset for companies because they can be used as indicators of quality and companiesâ revenue in the future. Consumersâ satisfaction can lead to the growth of repurchase intention and make consumers recommend the product to other people. Based on this phenomena, the problem statement that will be researched is "how is the influence consumer satisfaction to the word of mouth communication and repurchase intention of the products and service in London Beauty Centre beauty clinic in Yogyakarta. Problem solving begins with developing research model that based on theoretical review from previous research. From that model, two variables are developed, which are consumer satisfaction and repurchase intention. These two variables will be tested to solve the problem of this research. Respondents from this research are 114 members of London Beauty Centre Yogyakarta. The results from simple linear regression analysis show that consumer satisfaction is significantly influence word of mouth communication and repurchase intention. Consumer satisfaction is more dominant influencing the repurchase intention.